Advances in numerical dating of Quaternary glaciations in China - Yi, Chaolu; Zhu, Zhiyong; Wei, Ling; Cui, Zhijiu; Zheng, Benxing; Shi, Yafeng (Zeitschrift für Geomorphologie, Supplementary Issues, 2007)
The Tibetan Plateau, its surrounding mountains, and the high mountains in eastern China hold evidence of widespread Quaternary glaciations. Because of regional differences in climate and the impacted environment, the glacial periods determined by relative dating methods in China before the 1970s could not adequately be compared with those in other regions of the world. Radiocarbon dating and lichenometry became available for dating glacial tills during the 1970-80s, followed by thermoluminescence (TL), electron spin resonance (ESR) and cosmogenic radionuclides (CRN) after 2000. These new absolute dates now allow us to place China's glaciations into the pre-existing world-wide framework. Based on new dating results, we have determinedsix Quaternary glacial stages in China as follows: a) the Little Ice Age, with three sub-stages in the late nineteenth, late eighteenth and early sixteenth centuries; b) the Neoglacial, with five sub-stages with ages of 1.5-1.6 ka, 2.5-3.6 ka, 4.0-5.5 ka, 8.1-8.5 ka, and 10.4-11.5 ka; c) the 'Last Glaciation' (Wurm or Wisconsin), with four sub-stages with ages of 16-18 ka, 19-24 ka, 40-56 ka and 72-73 ka; d) the 'Penultimate Glaciation' (Kansan) with three sub-stages with ages of 136-154 ka, 266-277 ka and 316-333 ka; and e) during the Marine Isotope Stages (MIS) 12-16 Glaciation, with two sub-stages with ages of 460-520 ka and 593-678 ka. Most of the Quaternary glaciations since the last glaciation were synchronous with global glacial events, except for a glacial advance during the MIS 3b (a sub-stage with an age of 40-56 ka in the Last Glaciation) at the southern and eastern borders of Tibet, which might be caused by greater precipitation during the relatively cold period. Geography, Physical Geosciences, Multidisciplinary SCI(E) CPCI-S(ISTP) 7